Survival Strategic Buruh PTPN XII Sempol Ijen Bondowoso: Survival Strategies of Workers at PTPN XII Sempol Ijen Bondowoso - M.F. Hidayatullah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
The welfare of plantation workers has never been adequate, including at PTPN XII. The wages they receive are far below the regional minimum wage (UMR) set by the government. Despite this, they continue to survive and live the